Inspiring Interest in Computing using Music: A Case Study on Students Lacking Prior Music Education - Krug, Douglas Lusa; Kulibaba, Reuel J.; Linzmeyer, Denis A.; Mouza, Chrystalla; Shepherd, David C. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2023)
Broadening interest in computer science is a major research goal of the 21st century. Many initiatives use traditional “hooks” to attract students, such as video games and robotics. Unfortunately, this tends to attract only those already interested in computer science. One alternative domain gaining momentum in computer science education research is music, which is showing interesting results with participants that have previous music knowledge. This paper presents a case study of teaching computer programming with music, in Brazil, to students with limited formal music experience. Through data collected in surveys, focus groups, and researchers’ observations, we show that in this context students can still learn and thrive as musical programmers.